A Molecular Simulation Approach to Bond Reorganization in Epoxy Resins: From Curing to Deformation and Fracture - Konrad, Julian; Meißner, Robert H.; Bitzek, Erik; Zahn, Dirk (ACS Polymers Au, 2021)
We model bond formation and dissociation processes in thermosetting polymer networks from molecular dynamics simulations. For this, a coarsened molecular mechanics model is derived from quantum calculations to provide effective interaction potentials that enable million-atoms scale simulations. The importance of bond (re)organization is demonstrated for (i) simulating epoxy resin formation─for which our approach leads to realistic network models which can now account for degrees of curing up to 98%. Moreover, (ii) we elucidate the competition of bond dissociation and bond reformation during plastic deformation and fracture. On this basis, we rationalize the molecular mechanisms that account for the irreversible nature of damaging epoxy polymers by mechanical load.
Keywords: epoxy resin; reactive force-field; molecular dynamics; curing fracture; tensile testing

Assessing the mechanical properties of molecular materials from atomic simulation - Konrad, Julian; Zahn, Dirk (AIMS Materials Science, 2021)
We review approaches to deriving mechanical properties from atomic simulations with a special emphasis on temperature-dependent characterization of polymer materials. The complex molecular network of such materials implies only partial, rather local ordering stemming from the entanglement of molecular moieties or covalent bonding of network nodes, whereas the polymer strands between the nodes may undergo nm-scale reorganization during thermal fluctuations. This not only leads to a strong temperature-dependence of the elastic moduli, but also gives rise to visco-elastic behavior that complicates characterization from molecular dynamics simulations. Indeed, tensile-testing approaches need rigorous evaluation of strain-rate dependences, provoking significant computational demands. Likewise, the use of fluctuations observed from unbiased constant-temperature, constant-pressure molecular dynamics simulation is not straight-forward. However, we suggest pre-processing from Fourier-filtering prior to taking Boltzmann-statistics to discriminate elastic-type vibrations of the simulation models for suitable application of linear-response theory.
Keywords: molecular materials; polymers; mechanical properties; molecular dynamics simulations

Bottom-to-top modeling of epoxy resins: From atomic models to mesoscale fracture mechanisms - Konrad, Julian; Zahn, Dirk (Journal of Chemical Physics, 2024)
We outline a coarse-grained model of epoxy resins (bisphenol-F-diglycidyl-ether/3,5-diethyltoluene-2,4-diamine) to describe elastic and plastic deformation, cavitation, and fracture at the μm scale. For this, molecular scale simulation data collected from quantum and molecular mechanics studies are coarsened into an effective interaction potential featuring a single type of beads that mimic 100 nm scale building blocks of the material. Our model allows bridging the time-length scale problem toward experimental tensile testing, thus effectively reproducing the deformation and fracture characteristics observed for strain rates of 10−1 to 10−5 s−1. This paves the way to analyzing viscoelastic deformation, plastic behavior, and yielding characteristics by means of “post-atomistic” simulation models that retain the molecular mechanics of the underlying epoxy resin at length scales of 0.1-10 µm.
CRIS-Team Scopus Importer:2024-01-19

Interfaces in reinforced epoxy resins: from molecular scale understanding towards mechanical properties - Konrad, Julian; Zahn, Dirk (Journal of Molecular Modeling, 2023)
CONTEXT: We report on atomic level of detail analyses of polymer composite models featuring epoxy resin interfaces to silica, iron oxide, and cellulose layers. Using "reactive" molecular dynamics simulations to explore epoxy network formation, resin hardening is investigated in an unprejudiced manner. This allows the detailed characterization of salt-bridges and hydrogen bonds at the interfaces. Moreover, our sandwich-type composite systems are subjected to tensile testing along the interface normal. To elucidate the role of relaxation processes, we contrast (i) direct dissociation of the epoxy-metal oxide/cellulose contact layer, (ii) constant strain-rate molecular dynamics studies featuring (visco-)elastic deformation and bond rupture of the epoxy resin, and (iii) extrapolated relaxation dynamics mimicking quasi-static conditions. While the fracture mechanism is clearly identified as interface dissociation of the composite constituents, we still find damaging of the nearby polymer phase. The observed plastic deformation and local cavitation are rationalized from the comparably large stress required for the dissociation of salt-bridges, hydrogen bonds, and van der Waals contacts. Indeed, the delamination of the contact layers of epoxy resins with slabs of silica, magnetite, and cellulose call for a maximum stress of 33, 26, and 21 MPa, respectively, as compared to 84 MPa required for bulk epoxy yielding. METHODS: Molecular dynamics simulations using the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) code were augmented by a Monte Carlo-type procedure to probe epoxy bond formation (Macromolecules 53(22): 9698-9705). The underlying interaction models are split into conventional Generalized Amber Force Fields (GAFF) for non-reacting moieties and a recently developed reactive molecular mechanics potential enabling epoxy bond formation and cleavage (ACS Polymers Au 1(3): 165-174).
CRIS-Team Scopus Importer:2023-07-21
Keywords: Epoxy resins; Molecular simulation; Reinforced polymers

Molecular Simulation of Thermosetting Polymer Hardening: Reactive Events Enabled by Controlled Topology Transfer - Meißner, Robert H.; Konrad, Julian; Boll, Benjamin; Fiedler, Bodo; Zahn, Dirk (Macromolecules, 2020)
We present a nonhybrid quantum mechanical/molecular mechanics (QM/MM) type approach to tackle chemical reactions with substantial molecular reorganization. For this, molecular dynamics simulations with smoothly switched interaction models are used to suggest suitable product states, while a Monte Carlo algorithm is employed to assess the reaction likeliness subject to energetic feasibility. As a demonstrator, we study the cross-linking of bisphenol F diglycidyl ether (BFDGE) and 4,6-diethyl-2-methylbenzene-1,3-diamine (DETDA). The modeling of epoxy curing was supplemented by differential scanning calorimetry (DSC) measurements, which confirm the degrees of cross-linking as a function of curing temperature. Likewise, the heat of formation and the mechanical properties of the resulting thermosetting polymer are found to be in good agreement with previous experiments.
Created from Fastlane, Scopus look-up

Molecular Simulations and Network Analyses of Surface/Interface Effects in Epoxy Resins: How Bonding Adapts to Boundary Conditions - Konrad, Julian; Moretti, Paolo; Zahn, Dirk (Polymers, 2022)
In this study, we unravel the atomic structure of a covalent resin near boundaries such as surfaces and composite constituents. For this, a molecular simulation analysis of epoxy resin hardening under various boundary conditions was performed. On the atomic level of detail, molecular dynamics simulations were employed to study crosslinking reactions and self-organization of the polymer network within nm scale slab models. The resulting structures were then coarsened into a graph theoretical description for connectivity analysis of the nodes and combined with characterization of the node-to-node vector orientation. On this basis, we show that the local bonding of epoxy resins near interfaces tends to avoid under-coordinated linker sites. For both epoxy–vacuum surface models and epoxy–silica/epoxy cellulose interfaces, we find almost fully cured polymer networks. These feature a local increase in network linking lateral to the surface/interface, rather than the dangling of unreacted epoxy groups. Consequently, interface tension is low (as compared to the work of separating bulk epoxy), and the reactivity of the resin surface appears negligible.<br

Multi-Scale Modelling of Plastic Deformation, Damage and Relaxation in Epoxy Resins - Konrad, Julian; Pfaller, Sebastian; Zahn, Dirk (Polymers, 2022)
Epoxy resin plasticity and damage was studied from molecular dynamic simulations and interpreted by the help of constitutive modelling. For the latter, we suggested a physically motivated approach that aims at interpolating two well-defined limiting cases; namely, pulling at the vanishing strain rate and very rapid deformation; here, taken as 50% of the speed of sound of the material. In turn, to consider 0.1-10-m/s-scale deformation rates, we employed a simple relaxation model featuring exponential stress decay with a relaxation time of 1.5 ns. As benchmarks, deformation and strain reversal runs were performed by molecular dynamic simulations using two different strain rates. Our analyses show the importance of molecular rearrangements within the epoxy network loops for rationalizing the strain-rate dependence of plasticity and residual stress upon strain reversal. To this end, our constitutive model reasonably reproduced experimental data of elastic and visco-elastic epoxy deformation, along with the maximum stress experienced before fracturing. Moreover, we show the importance of introducing damage elements for mimicking the mechanical behavior of epoxy resins.
CRIS-Team WoS Importer:2022-09-09